Design of Unmanned Vehicle System for Disaster Detection - Ming-Chih Chen; Chien-Hsing Chen; Ming-Sheng Huang; Jheng-Yu Ciou; Guo-Tai Zhang (International Journal of Distributed Sensor Networks)
This work presents a novel unmanned vehicle system, capable of detecting risks in disaster areas. The rescuer can operate an unmanned vehicle to reach the disaster area via remote control. An android-based application program is used to control the remote vehicle via wireless network. The vehicle system is capable of detecting a variety of gases by the sensors deployed on it. The gas sensors can detect methane, ethane, and carbon dioxide. After detecting the gases, the vehicle passes the collected information to the rescuer for deciding which equipment can be used in the disaster. The gas detection sensors can reduce the injury risks of rescuers before they go into the disaster area. The vehicle is also equipped with a video surveillance camera to monitor the scene and find injured persons. A robotic arm is mounted on the head of the vehicle to grip objects and gather samples. Our unmanned system can effectively reduce casualties by gathering information about the disaster beforehand.